2011
DOI: 10.1002/ange.201002845
|View full text |Cite
|
Sign up to set email alerts
|

Photochemische Reaktionen als Schlüsselschritte in der Naturstoffsynthese

Abstract: Photochemische Reaktionen bereichern in signifikanter Weise das Repertoire zur Knüpfung von Kohlenstoff‐Kohlenstoff‐Bindungen und machen ungewöhnliche, auf herkömmlichem Weg nicht erhältliche Molekülgerüste zugänglich. In diesem Aufsatz werden die wichtigsten Umsetzungen der Photochemie vorgestellt, die auf breiter Front Einzug in die Naturstoffsynthese gehalten haben. Beispielhaft werden einzelne Totalsynthesen diskutiert, wobei besonderes Augenmerk auf den photochemischen Schlüsselschritt sowie dessen Stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(38 citation statements)
references
References 667 publications
3
34
0
1
Order By: Relevance
“…[2,4] In principle, such criteria could also be met by the related photochemical rearrangement of 1 a to 5H-furanone 4 a, yet this reaction has lain almost dormant since its introduction by because of the low yields attained in each of the published examples (27-51 %, Scheme 2). [6,7] In addition, our results challenge the long-established view that the electrocyclic opening of cyclobutenones is a torquoselective process, with the thermochemical and photochemical rearrangements displaying complimentary torquoselectivity, [1e] as implicated by the aforementioned examples (Scheme 1). [6,7] In addition, our results challenge the long-established view that the electrocyclic opening of cyclobutenones is a torquoselective process, with the thermochemical and photochemical rearrangements displaying complimentary torquoselectivity, [1e] as implicated by the aforementioned examples (Scheme 1).…”
supporting
confidence: 47%
“…[2,4] In principle, such criteria could also be met by the related photochemical rearrangement of 1 a to 5H-furanone 4 a, yet this reaction has lain almost dormant since its introduction by because of the low yields attained in each of the published examples (27-51 %, Scheme 2). [6,7] In addition, our results challenge the long-established view that the electrocyclic opening of cyclobutenones is a torquoselective process, with the thermochemical and photochemical rearrangements displaying complimentary torquoselectivity, [1e] as implicated by the aforementioned examples (Scheme 1). [6,7] In addition, our results challenge the long-established view that the electrocyclic opening of cyclobutenones is a torquoselective process, with the thermochemical and photochemical rearrangements displaying complimentary torquoselectivity, [1e] as implicated by the aforementioned examples (Scheme 1).…”
supporting
confidence: 47%
“…[19d,20] Initially,w et ried the reaction conditions illustrated in Scheme 1, and found no trace of cycloadducts were detected (entry 1). [21] Thehigh reactivity of the 1 could be used to rationalize the present results in forming both [4+ +2] and [2+ +2] cycloaddition products.T oi mprove the yields,w ep erformed the reaction under neat conditions and found that the reaction occurred at 45 8 8Ctogive an improved yield (entry 3). It is interesting to observe the formation of 20 because the thermodynamic [2+ +2] cycloaddition is relatively rare.…”
mentioning
confidence: 61%
“…[1] This is largely due to agrowing appreciation of the synthetic utility of photoredox catalysts,w hich, upon photoexcitation, function as single-electron or energy transfer catalysts to provide access to free-radical intermediates. [3] However,r ecent developments have taken advantage of the visible light absorptivity of specific functional groups that act as photoactive handles to enable photoinduced electron transfer (PET). [3] However,r ecent developments have taken advantage of the visible light absorptivity of specific functional groups that act as photoactive handles to enable photoinduced electron transfer (PET).…”
mentioning
confidence: 99%